2015
DOI: 10.1039/c5cc04590h
|View full text |Cite
|
Sign up to set email alerts
|

Towards efficient chemical synthesis via engineering enzyme catalysis in biomimetic nanoreactors

Abstract: Biocatalysis with immobilized enzymes as catalysts holds enormous promise in developing more efficient and sustainable processes for the synthesis of fine chemicals, chiral pharmaceuticals and biomass feedstocks. Despite the appealing potentials, nowadays the industrial-scale application of biocatalysts is still quite modest in comparison with that of traditional chemical catalysts. A critical issue is that the catalytic performance of enzymes, the sophisticated and vulnerable catalytic machineries, strongly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 88 publications
(184 reference statements)
0
20
0
Order By: Relevance
“…Structure of open form of BCL. The catalytic triad in the active site is shown in a red stick representation (Liu, Yang, & Li, )…”
Section: Enzymes In Biotechnological Processesmentioning
confidence: 99%
“…Structure of open form of BCL. The catalytic triad in the active site is shown in a red stick representation (Liu, Yang, & Li, )…”
Section: Enzymes In Biotechnological Processesmentioning
confidence: 99%
“…Li, for example, is experimenting with housing enzymes inside nanoparticles 14 to help them last longer. Others are synthesizing completely artificial enzymes 15 using techniques from synthetic biology.…”
Section: Even-handednessmentioning
confidence: 99%
“… 47 49 This decrease of catalytic reaction and the resulting slow reaction that occurred particularly in porous silica nanoparticles, as previously reported, 13 depended on different factors such as modification of the enzyme structure, adsorption of the enzyme on the porous materials crowding effects and diffusion of molecules through the membranes. 50 , 51 Furthermore, the decrease of V max values for H 2 O 2 depended on the disruption of the enzyme that was affected by the confinement of HRP inside the nanoreactor compartment, 13 or due to the diffusional resistance of substrates. 52 54 In such a way, we previously demonstrated that UnPSi nanoparticles coated with cancer cell membranes favored the interaction between AR with the hydrophobic counterpart of bilayer membrane and hindered the enzymatic interaction with HRP, 13 thus causing slow values of V max of nanoparticles compared to the free HPR in solution.…”
Section: Resultsmentioning
confidence: 99%